Optimization of Oleyl Ester using Statistical Approach of Response Surface Methodology - Salina Mat Radzi; Hanina Mohd Noor; Maryam Mohamed Rehan; Mohd Akmal Rosli (International Institute of Chemical, Biological & Environmental Engineering, 2024)
Oleyl oleate was synthesized by green process of lipase-catalyzed esterification reaction between oleic acid and oleyl alcohol. Dual enzymes system consisting of Novozym 435 and Lipozyme TL IM were used due to its specificity towards an ester bond. The reaction was optimized by statistical approach of RSM with four important parameters such as reaction time, reaction temperature, amount of enzymes and molar ratio of substrates. 97.52 % of oleyl oleate was achieved at the most optimum condition (58.67 min, 59.68 °C, 0.37 g enzymes and 2.88 molar ratio of substrates). Regression analysis shows all parameters were significant (Prob P < 0.05) except for the reaction temperature.